Vascular epiphytes of two nearby riverside forests, Iguaçu River Basin, Paraná. - Kersten, Rodrigo de Andrade (2009)
The vascular epiphyte survey was carried out in riverside forest near São Geronimo River, Guarapuava and Pinhão – Paraná (25º39’ S e 51º25 W). We recognized two different forests, floodplain and hillside, both varying from 1,100-1,200 m. a.s.l. For the survey we analyzed 90 assorted trees for each forest. Each tree was divided into three zones. On these zones the dominance was estimated by attributing scores for the occurring species. We listed 54 vascular species (15 pteridophytes, three magnoliids, 30 monocots and 7 eudicots). For the floodplain 42 species were recorded, 30 for the hillside forest, and 8 for both forests. Microgramma squamulosa (Kaulf.) de la Sota was the most important species in both forests, Campyloneurum austrobrasilianum (Alston) de la Sota followed in the floodplain and Pleopeltis hirsutissima (Raddi) de la Sota in the hillside forest. On the same phorophyte, the number of epiphyte species varied from zero to 19 in the floodplain forest and from zero to 11 in the hillsideforest.